Analisis Persfektif Pemikiran Ismail Raji Al-Faruqi dan Nurcholis Madjid Tentang Islamisasi Ilmu Pengetahuan - Jamaludin HS; Muhibut Tibri; Syukri Iska; Yudelas Harmi; Yulfian Yulfian (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study attempts to comparatively analyze the thoughts of two important figures in the discourse of modern Islamic thought, namely Ismail Raji Al-Faruqi and Nurcholis Madjid, who each offer alternative solutions to overcome the challenges of integration between Islam and science and the development of Islamic education. Using a qualitative descriptive-analytical method based on literature study, this study finds that Al-Faruqi proposed the concept of the Islamization of science based on the principle of tauhid as an epistemological, methodological, and ontological basis. The Islamization program he formulated emphasized the importance of mastering modern science, exploring Islamic treasures, determining the relevance of Islamic values ​​in various disciplines, and synthesizing modern science and Islamic values. On the other hand, Nurcholis Madjid emphasized the importance of renewing Islamic education through a humanist, inclusive, egalitarian, and pluralist approach, which is in line with the spirit of Islam as rahmatan lil ‘ālamīn and the values ​​of Indonesianness. The comparison shows that Al-Faruqi placed greater emphasis on reconstructing the epistemology of science, while Madjid focused more on developing humanistic and contextual Muslim individuals. Both rejected the concept of value-free science and viewed Islam as the ethical foundation for the development of science and education.